Program-assisted sizing of a photovoltaic-powered water pumping system - Chikuni, Edward (Journal of Energy in Southern Africa, 2017)
Climate change has had perhaps the most adverse effect on African rural communities where we witness persistent droughts and erratic rain patterns. Peasants often have to walk many kilometres to fetch water of a suspect quality. In these circumstances underground water supplies provide the best hope for them. Often, however, water tables may have receded to such an extent that wells are not a practical proposition. Besides, water is needed not just for domestic use such as food preparation and cleaning, but also for livestock and watering of small gardens. In this paper we present methodology for sizing and designing a photovoltaic pumping system based on components available in Southern Africa. We also show that solar pumping technology has gone past the experimental and prototype stage. Further we strongly put forward the proposition that the technology has clearly matured and in terms of cost, is fast approaching that of choice over other technologies relying on the grid. Currently the region faces an energy shortage and we see not only electricity cuts but those customers that actually are supplied with electricity face increasing and unacceptable tariffs. To make it more convenient we have consolidated the design process in a Visual Basic tool which is easy to use and apply.